The Impact of the Covid-19 Pandemic on Character Education in Online Learning at Darul Hikam High School - Ditha Nurul Fazrin; Wahju Gunawan; Muhammad Fedryansyah (Budapest International Research and Critics University, 2022)
The purpose of this study was to observe the implementation of character education during online learning and its impact on the formation of students' character. This type of research is descriptive qualitative research with interview data collection techniques, observation and documentation. The results showed that there was a change in the implementation of character education in online learning such as the media used, methods and indicators of online learning character. The character values carried by the school can be implemented during online learning with various learning methods and student programs. The increasing use of technology helps the implementation of character education during online learning. The impact is that there are differences in levels of character formation such as character enhancement in the value of being intelligent and patient. This is because of the support from the technology and media used. However, there is a decrease in the value of discipline and trust. There needs to be a change in character indicators after online learning.